2015
DOI: 10.1371/journal.pone.0144446
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hematological Variables with Team-Sport Specific Fitness Performance

Abstract: PurposeWe investigated association of hematological variables with specific fitness performance in elite team-sport players.MethodsHemoglobin mass (Hbmass) was measured in 25 elite field hockey players using the optimized (2 min) CO-rebreathing method. Hemoglobin concentration ([Hb]), hematocrit and mean corpuscular hemoglobin concentration (MCHC) were analyzed in venous blood. Fitness performance evaluation included a repeated-sprint ability (RSA) test (8 x 20 m sprints, 20 s of rest) and the Yo-Yo intermitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 40 publications
(75 reference statements)
1
19
1
Order By: Relevance
“…Computation of YYIR2 test global means, SDs and quantiles (Figure 3) involved 116 studies/subgroups reporting on 2,478 participants (median age = 23.2 years, IQR = 20.7–26.0 years) (Young et al, 2005; De Souza et al, 2006; Krustrup et al, 2006; Thomas et al, 2006; Mohr et al, 2007, 2016; Iaia et al, 2008, 2015, 2017; Morton et al, 2009; Rampinini et al, 2010; Rebelo et al, 2010; Thomassen et al, 2010; Christensen et al, 2011; Chuman et al, 2011; Mooney et al, 2011, 2013a,b; Roberts et al, 2011; Ueda et al, 2011; Gunnarsson et al, 2012; Ingebrigtsen et al, 2012, 2013, 2014; Nakamura et al, 2012; Saunders et al, 2012; Wells et al, 2012, 2014; Bassini et al, 2013; Buchheit et al, 2013; McGawley and Andersson, 2013; Mohr and Krustrup, 2013, 2014, 2016; Owen et al, 2013; Pivovarniček et al, 2013; Yuki et al, 2013; Fanchini et al, 2014; Karavelioglu et al, 2014; Lollo et al, 2014; Miloski et al, 2014; Nunes et al, 2014; Sampaio et al, 2014; Skovgaard et al, 2014; Brocherie et al, 2015a,b; Cholewa et al, 2015; Coelho et al, 2015; Gatterer et al, 2015; Hogarth et al, 2015a,b; Jamurtas et al, 2015; Krustrup and Mohr, 2015; Leme et al, 2015; Mara et al, 2015; Matta et al, 2015; McLean et al, 2015; Michalsik et al, 2015; Mohr, 2015; Rogan, 2015; Stein et al, 2015; Boer and Van Aswegen, 2016; Bouaziz et al, 2016; Chan et al, 2016; Inness et al, 2016; Joo, 2016; Kilit and Arslan, 2016; Lockie et al, 2016a,b,...…”
Section: Resultsmentioning
confidence: 99%
“…Computation of YYIR2 test global means, SDs and quantiles (Figure 3) involved 116 studies/subgroups reporting on 2,478 participants (median age = 23.2 years, IQR = 20.7–26.0 years) (Young et al, 2005; De Souza et al, 2006; Krustrup et al, 2006; Thomas et al, 2006; Mohr et al, 2007, 2016; Iaia et al, 2008, 2015, 2017; Morton et al, 2009; Rampinini et al, 2010; Rebelo et al, 2010; Thomassen et al, 2010; Christensen et al, 2011; Chuman et al, 2011; Mooney et al, 2011, 2013a,b; Roberts et al, 2011; Ueda et al, 2011; Gunnarsson et al, 2012; Ingebrigtsen et al, 2012, 2013, 2014; Nakamura et al, 2012; Saunders et al, 2012; Wells et al, 2012, 2014; Bassini et al, 2013; Buchheit et al, 2013; McGawley and Andersson, 2013; Mohr and Krustrup, 2013, 2014, 2016; Owen et al, 2013; Pivovarniček et al, 2013; Yuki et al, 2013; Fanchini et al, 2014; Karavelioglu et al, 2014; Lollo et al, 2014; Miloski et al, 2014; Nunes et al, 2014; Sampaio et al, 2014; Skovgaard et al, 2014; Brocherie et al, 2015a,b; Cholewa et al, 2015; Coelho et al, 2015; Gatterer et al, 2015; Hogarth et al, 2015a,b; Jamurtas et al, 2015; Krustrup and Mohr, 2015; Leme et al, 2015; Mara et al, 2015; Matta et al, 2015; McLean et al, 2015; Michalsik et al, 2015; Mohr, 2015; Rogan, 2015; Stein et al, 2015; Boer and Van Aswegen, 2016; Bouaziz et al, 2016; Chan et al, 2016; Inness et al, 2016; Joo, 2016; Kilit and Arslan, 2016; Lockie et al, 2016a,b,...…”
Section: Resultsmentioning
confidence: 99%
“…Training and iron status have also been shown to cause changes in hemoglobin (Hb), hematocrit (HCT) and mean corpuscular hemoglobin concentration (MCHC) (Brocherie et al, 2015;Heisterberg et al, 2013;Hinrichs et al, 2010). Slight decreases in hemoglobin and hematocrit are expected in athletes due to increases in plasma volume associated with training, a condition commonly termed "sports anemia" (Heisterberg et al, 2013).…”
Section: Hemoglobin (Hb) Hematocrit (Hct) and Mean Corpuscular Hemogmentioning
confidence: 99%
“…Several researchers have correlated hematologic parameters (i.e. Hb, HCT and MCHC) to decreases in VO 2 max and scores on the Yo-Yo Intermittent Recovery Level 2 test (YYIR2) (Brocherie et al, 2015;Heisterberg et al, 2013). Brocherie et al (2015) found that absolute hemoglobin concentration and mean corpuscular hemoglobin concentration were moderately correlated with YYIR2 while athletes with lower mass Hb showed a decreased time to exhaustion.…”
Section: Hemoglobin (Hb) Hematocrit (Hct) and Mean Corpuscular Hemogmentioning
confidence: 99%
See 1 more Smart Citation
“…This may suggest that RSA is more related to short sprint performance than endurance capacity (27,33). However, others have reported large magnitude associations with RSA and aerobic fitness (8,16,21). Weak relationships between RSA and counter-movement jump height have also been observed (18), suggesting that leg power is not a major determinant of RSA.…”
Section: Introductionmentioning
confidence: 99%